Selected indicators of the seniors tourist activity in Poland and in others european countries - Krzysztof Parzych; Rafał Gotowski (Kazimierz Wielki University, 2016)
In this work was taken an issues of the tourist activity of the older people. For this purpose was used the statistics of Eurostat and from the Statistic Yearbook " Tourism in polish households" The analysis shows the polish older people more seldom partcipate in the tourist traffic comparing to the west european countriwes older people. The main characteristics shows low level of the polish older people's tourist activity. They seldom participate in tourism. They most often go to their families form shortterm stays or for holiday.They prefer travels in the summer months. Most often opolish older people independently organizae their journeys and use the overnight accomodation in the houses of their friends and relatives. They most often go to the cities, coastal resorts and others mountain and lakeshore resorts. Besides it polsih older people prefer passive behaviours in their free time as reding books, watching television and listening to the radio and resting.